Liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel material as well as preparation method and application thereof

Through the design of liquid metal/MXene/sodium alginate/polyacrylamide composite hydrogel materials, the shortcomings of existing materials in EMI shielding, mechanical properties and biocompatibility are solved, and high-performance flexible electronic device materials are realized, suitable for multi-function wearable devices.

CN119684737AActive Publication Date: 2025-03-25TONGJI UNIV

Patent Information

Application Number
CN202411935588.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-25
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

Existing flexible electronics materials have shortcomings in the face of high EMI shielding, good mechanical strength and flexibility, ease of processing and multifunctional integration, especially when dealing with increasing harmful electromagnetic interference and radiation, the single biocompatibility and function of the materials limit its application range.

Method used

The liquid metal/MXene/sodium alginate/polyacrylamide composite hydrogel material is used to coat liquid metal microspheres with sodium alginate to bidirectionally enhance the hydrogel, forming a graded porous structure and "island bridge" structure, improving the material's elongation and electromagnetic shielding performance.

Benefits of technology

The composite hydrogel material with high toughness, good stretching and conductivity has excellent electromagnetic shielding performance, strain sensing performance and temperature sensing performance, is suitable for multifunctional integrated wearable devices and has good biocompatibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684737A_ABST
    Figure CN119684737A_ABST
Patent Text Reader

Abstract

The invention relates to a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel material as well as a preparation method and application thereof. The hydrogel material comprises liquid metal microspheres, a hierarchical porous network formed by sodium alginate and polyacrylamide, and flaky MXene. The preparation method comprises the following steps: S1, adding liquid metal into an aqueous solution, and carrying out ultrasonic dispersion to obtain dispersion liquid; s2, adding the dispersion liquid into a sodium alginate solution, and performing ultrasonic treatment to obtain a sodium alginate-coated liquid metal aqueous solution; s3, acrylamide is dissolved in deionized water, then the aqueous solution of the liquid metal wrapped by sodium alginate is added, then a cross-linking agent, an initiator and MXene are added, and the mixture is stirred to be uniform; and S4, pouring into a mold, and heating to form the hydrogel. The composite hydrogel material prepared by the invention has the advantages of high stretch rate, strong electromagnetic shielding performance and the like, and can be used as electronic skin for electromagnetic shielding, human health monitoring, man-machine communication and soft robots.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of flexible electronic devices, and in particular relates to a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel material and a preparation method and application thereof. Background Art

[0002] In the digital age, the widespread electromagnetic radiation from electronic devices has raised serious concerns about its multiple adverse effects on human health, including neurodegenerative diseases, carcinogenesis, and other worrisome conditions. Therefore, there is an urgent need for EMI shielding materials with high EMI shielding effectiveness (SE), good mechanical strength and flexibility, easy processing, and integrated multifunctionality.

[0003] As a typical flexible material, conductive hydrogel has become one of the candidate materials for flexible electronic devices due to its flexibility, scalability, conductivity and biocompatibility. However, traditional conductive hydrogels have low mechanical properties and single functions, which limits their application range.

[0004] In order to meet these challenges, double-network hydrogels with excellent mechanical properties have attracted people's attention. The porous double-network hydrogel can achieve excellent high stretchability to meet the use under extreme conditions under the interaction of a rigid polyelectrolyte network structure with a high cross-linking density as the first network and a low-crosslinked or non-crosslinked neutral network structure with good deformation and stretchability as the high-strength second network, providing a platform for multifunctional integrated flexible electronic shielding materials. However, hydrogels with only simple networks have problems such as insufficient mechanical properties and single functions. At the same time, hydrogels used in fields such as sensors and wearable devices will face increasing harmful electromagnetic interference (EMI) or radiation. These electromagnetic waves will not only affect the normal operation of hydrogels, but also cause harm to human health.

[0005] Therefore, there is an urgent need to design multifunctional hydrogels with excellent mechanical properties, high EMI shielding effectiveness (SE), and good biocompatibility for the next generation of smart wearable and even implantable devices. Summary of the invention

[0006] Based on the defects in the above-mentioned prior art, the purpose of this application is to provide a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel material and its preparation method and application. The present invention provides a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel material, the composite hydrogel has high toughness and good elongation and conductivity, and is biocompatible.

[0007] The technical solution adopted by the present invention to achieve the above-mentioned purpose is described in detail below; the purpose of the present invention can be achieved by the following technical solution:

[0008] One of the technical solutions of the present invention provides a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel material, which includes a hierarchical porous structure and an "island bridge" structure; the hierarchical porous structure is composed of a network reinforced by liquid metal microspheres and a hydrogel double network, and the "island bridge" structure is composed of liquid metal microspheres and MXene nanosheets.

[0009] Furthermore, the pores of the graded porous structure are 5 to 20 μm.

[0010] Furthermore, the MXene nanosheets are evenly distributed in the hydrogel network, forming an "island-bridge" structure with the liquid metal microspheres.

[0011] The island-bridge structure is a special nanostructure in chemical materials. It usually refers to the morphology in which nanoislands distributed on a two-dimensional surface are interconnected by connecting structures (bridges). This structure can affect the electrical, optical and magnetic properties of the material and is of great significance in the study of nanomaterials. Specifically: Nanoislands are local protrusions with sizes on the nanoscale, which can be single molecular clusters or larger particles; they can be formed from various materials, such as metals, semiconductors or insulators, and are usually formed naturally during thin film deposition or self-assembly. The bridge structure between islands is a connecting part formed by the continuous distribution of matter. These connections can be linear, branched or network-like. They provide a continuous path for matter at the nanoscale and may affect the transmission of electrons and the transfer of energy.

[0012] The second technical solution of the present invention provides a method for preparing a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel material, comprising the following steps:

[0013] S1. Add liquid metal to deionized water, shake well, and use a cell disruptor to sonicate to obtain a uniformly dispersed liquid metal microsphere dispersion;

[0014] S2. The liquid metal microsphere dispersion is mixed with a sodium alginate solution, and then subjected to ultrasonic treatment to obtain an aqueous solution of sodium alginate encapsulated liquid metal;

[0015] S3. Dispersing acrylamide monomer, crosslinking agent, initiator and MXene solution into the aqueous solution of sodium alginate-encapsulated liquid metal and stirring until completely dissolved to obtain a mixed solution;

[0016] S4. The mixed solution is quickly poured into the mold, and the hydrogel obtained after heating is a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel material.

[0017] Furthermore, the liquid metal in step S1 is a 16°C gallium-indium alloy; the gallium-indium alloy is solid at room temperature (approximately 16°C or 61°F), and turns into a liquid when the temperature is slightly increased. Gallium-indium alloys exhibit super-tensile properties and can exhibit stretching capabilities exceeding their inherent strength under certain conditions, which is mainly attributed to their surface tension-driven deformation mechanism. When subjected to tension, elongated droplets spontaneously form on the surface of the gallium-indium alloy. This phenomenon is called "droplet stretching" or "capillary-driven deformation of liquid metal", allowing the alloy to be stretched to a certain extent without breaking. In some applications, such as soft electronics, biomedical devices, and wearable technology, this property of gallium-indium alloys is fully utilized.

[0018] Furthermore, the amount of liquid metal and deionized water in step S1 is in the ratio of (0.5-2) g: 5 mL;

[0019] Furthermore, the cell disruptor ultrasonication time in step S1 is 5 to 10 minutes.

[0020] Furthermore, the concentration of the sodium alginate solution in step S2 is 3-5wt%;

[0021] Furthermore, the liquid metal microsphere dispersion and the sodium alginate solution in step S2 are used in equal volumes;

[0022] Furthermore, the ultrasonic treatment time in step S2 is 5 to 10 minutes.

[0023] Furthermore, in step S3, the cross-linking agent is any one of N,N-methylenebisacrylamide or dimethyl sulfoxide; the initiator is any one of ammonium persulfate or sodium perbromide; the concentration of the MXene solution is 0 to 14 mg / mL, and can be 0, the solvent is deionized water, and the solute is the MXene material; the MXene material is obtained by chemically etching the MAX phase material.

[0024] Furthermore, the MAX phase material is a complex metal carbonitride, and its chemical formula can be generally expressed as MnAX, where M represents a transition metal, A represents a main group element such as aluminum, titanium, scandium, vanadium, chromium, etc., and X represents nitrogen or carbon. The characteristics of MAX phase materials include high hardness, high melting point, excellent chemical stability, good thermal conductivity, and unique electrical and optical properties.

[0025] Furthermore, MAX phase materials specifically include but are not limited to the following: TiAlN (titanium aluminum nitride), CrCN (chromium carbonitride), Ti3AlC2 (titanium trialuminum dicarbide), Ti2AlN (titanium dialuminum nitride), V2AlC (vanadium dialuminum carbide), Mo2FeB2 (molybdenum diiron boride), and Nb2AlC (niobium dialuminum carbide).

[0026] Furthermore, in step S3, the dosage of the acrylamide monomer, the cross-linking agent, the initiator, the MXene solution and the aqueous solution of the sodium alginate-encapsulated liquid metal is in the following relationship: (0.5-3) g: (0.0055-0.0075) g: (0.010-0.0020) g: (2-3) mL: 10 mL.

[0027] Furthermore, the mold in step S4 is preferably a rectangular silicone mold;

[0028] Furthermore, the heating temperature in step S4 is 60-80° C. and the heating time is 30-60 minutes.

[0029] The third technical solution of the present application provides an application of the above-mentioned liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel material. The liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel material, as a multifunctional integrated flexible electronic device, has extremely high electromagnetic shielding performance, which can reach 86.6dB; and has strain sensing performance and temperature sensing performance, and can monitor the joint movement and ambient temperature of various parts of the human body.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] (1) The present invention prepares an ultra-stretched liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel material by a bidirectionally reinforced hydrogel method of sodium alginate-coated liquid metal microspheres. A hierarchical porous network reinforcement structure is formed as a whole, which greatly improves the stretchability and electromagnetic shielding performance of the hydrogel.

[0032] (2) The present invention prepares a hydrogel material with a hierarchical porous structure and high electrical conductivity. First, the hierarchical porous structure can effectively absorb electromagnetic waves of different wavelengths through the interaction of pores of different scales. Such a structure can achieve high-performance electromagnetic wave shielding, which is particularly important for application scenarios that require electromagnetic interference suppression. Secondly, the interior of the porous material has a large number of surfaces and interfaces, and electromagnetic waves will be reflected and scattered multiple times when passing through, increasing the dissipation path of electromagnetic energy, thereby enhancing the shielding efficiency. In addition, due to the enhanced performance of the liquid metal on the network, not only the stretchability of the hydrogel is greatly improved, but also the overall electrical conductivity of the hydrogel is improved, the conductive loss is increased, and the shielding performance is further improved. Finally, the composite hydrogel material is biocompatible, which is crucial for flexible electronic devices used in the human body.

[0033] (3) The "island bridge" structure of the present invention enables the polarization effect caused by the interlayer interaction of different materials to effectively enhance the loss of electromagnetic waves. When electromagnetic waves pass through these interfaces, multiple interface polarizations will be generated, which will be converted into heat energy, thereby increasing the electromagnetic shielding performance. In addition, the charge transfer and interaction between different materials can lead to changes in electron mobility, which helps to regulate the conductivity of the material and thus optimize the shielding performance.

[0034] (4) The preparation method of the present invention is simple, the operation is stable and controllable, and the liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel material finally obtained has the characteristics of high elongation, good shielding performance, rich functions, good biocompatibility, etc., which provides a new idea for the application of multifunctional integrated wearable devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a SEM characterization image of the sodium alginate-encapsulated liquid metal dispersion and the liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel finally obtained in Example 16 of the present invention;

[0036] Figure 1 The middle mark indicates:

[0037] (a) (b) are SEM images of sodium alginate-encapsulated liquid metal dispersion; (c) (d) are SEM images of liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel;

[0038] Figure 2 This is a stress-strain curve of the sodium alginate / polyacrylamide hydrogel finally prepared in Comparative Example 1;

[0039] Figure 3 The stress-strain curve of the liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel finally obtained in Examples 1-4;

[0040] Figure 4 The electromagnetic shielding performance diagram of the liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel finally prepared in Examples 13-16 and the sodium alginate / polyacrylamide hydrogel finally prepared in Comparative Example 1;

[0041] Figure 5 The flexible strain sensor of liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel monitors the signal of various parts of the human body;

[0042] Figure 5 The middle mark indicates:

[0043] (a) is a schematic diagram of the island bridge structure; (b) is a schematic diagram of sensing under different stretching rates; (c) is the GF factor of the liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel; (d)(e)(f)(g)(h)(i) are the monitoring signal diagrams of various parts of the human body by the flexible strain sensor of the liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel in Example 16, including (d) finger bending at different angles, (e) knee joint movement, (f) knee joint squat movement, (g) elbow joint movement, (h) rapid finger bending, and (i) heartbeat detection;

[0044] Figure 6 This is a diagram of the temperature sensor of liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel monitoring signals of ambient temperature and human body;

[0045] Figure 6 The middle mark indicates:

[0046] (a) is a schematic diagram of the temperature sensor of liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel; (b) is the resistance change of the temperature sensor of liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel at different temperatures; (c) is the resistance change of the temperature sensor of liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel under the cycle of 20 degrees-60 degrees; (d) is the resistance change when ice and hot water approach the temperature sensor of liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel; (e) is the resistance change of ice at a distance from liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel (f) The resistance change of the MXene / sodium alginate / polyacrylamide composite hydrogel temperature sensor at different distances; (g) The resistance change of the liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel temperature sensor under a cycle of 0 degrees to 20 degrees; (h) The different temperature detection ranges of the liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel temperature sensor; (i) The liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel temperature sensor detecting different human body temperatures. DETAILED DESCRIPTION

[0047] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is described in detail below in conjunction with specific embodiments. It should be noted that the following embodiments will help those skilled in the art to further understand the present invention, but do not limit the present invention in any form. It should be noted that for those of ordinary skill in the art, several variations and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0048] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0049] Embodiment 1:

[0050] First, add 0.5g of metal (gallium-indium alloy) to 5mL of deionized water, shake well, and use a cell disruptor to sonicate for 5min to obtain a uniformly dispersed liquid metal microsphere dispersion. Next, mix the above dispersion with 5mL of 4wt% sodium alginate solution, and then perform ultrasonic treatment for 5min to obtain an aqueous solution of sodium alginate encapsulated liquid metal. Subsequently, 2g of acrylamide monomer, 0.0065g of cross-linker N,N-methylenebisacrylamide, 0.015g of initiator ammonium persulfate, and 2.5mL of aqueous solution are dispersed into the above mixture and stirred until completely dissolved. Finally, the mixed solution is quickly poured into a rectangular silicone mold and heated at 60°C for 30 minutes to obtain a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel.

[0051] Embodiment 2:

[0052] First, add 0.5g of metal (gallium-indium alloy) to 5mL of deionized water, shake well, and use a cell disruptor to sonicate for 5min to obtain a uniformly dispersed liquid metal microsphere dispersion. Next, mix the above dispersion with 5mL of 4wt% sodium alginate solution, and then perform ultrasonic treatment for 5min to obtain an aqueous solution of sodium alginate-encapsulated liquid metal. Subsequently, 2g of acrylamide monomer, 0.0065g of cross-linker N,N-methylenebisacrylamide, 0.015g of initiator ammonium persulfate, and 2.5mLMXene (2mg / mL) solution were dispersed into the above mixture and stirred until completely dissolved. Finally, the mixed solution was quickly poured into a rectangular silicone mold and heated at 60°C for 30 minutes to obtain a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel.

[0053] Embodiment 3:

[0054] First, add 0.5g of metal (gallium-indium alloy) to 5mL of deionized water, shake well, and use a cell disruptor to sonicate for 5min to obtain a uniformly dispersed liquid metal microsphere dispersion. Next, mix the above dispersion with 5mL of 4wt% sodium alginate solution, and then perform ultrasonic treatment for 5min to obtain an aqueous solution of sodium alginate-encapsulated liquid metal. Subsequently, 2g of acrylamide monomer, 0.0065g of cross-linker N,N-methylenebisacrylamide, 0.015g of initiator ammonium persulfate, and 2.5mLMXene (7mg / mL) solution were dispersed into the above mixture and stirred until completely dissolved. Finally, the mixed solution was quickly poured into a rectangular silicone mold and heated at 60°C for 30 minutes to obtain a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel.

[0055] Embodiment 4:

[0056] First, add 0.5g of metal (gallium-indium alloy) to 5mL of deionized water, shake well, and use a cell disruptor to sonicate for 5min to obtain a uniformly dispersed liquid metal microsphere dispersion. Next, mix the above dispersion with 5mL of 4wt% sodium alginate solution, and then perform ultrasonic treatment for 5min to obtain an aqueous solution of sodium alginate encapsulated liquid metal. Subsequently, 2g of acrylamide monomer, 0.0065g of cross-linker N,N-methylenebisacrylamide, 0.015g of initiator ammonium persulfate, and 2.5mLMXene (14mg / mL) solution are dispersed into the above mixture and stirred until completely dissolved. Finally, the mixed solution is quickly poured into a rectangular silicone mold and heated at 60°C for 30 minutes to obtain a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel.

[0057] Embodiment 5:

[0058] First, add 1g of metal (gallium-indium alloy) to 5mL of deionized water, shake well, and use a cell disruptor to sonicate for 5min to obtain a uniformly dispersed liquid metal microsphere dispersion. Next, mix the above dispersion with 5mL of 4wt% sodium alginate solution, and then perform ultrasonic treatment for 5min to obtain an aqueous solution of sodium alginate encapsulated liquid metal. Subsequently, 2g of acrylamide monomer, 0.0065g of cross-linker N,N-methylenebisacrylamide, 0.015g of initiator ammonium persulfate, and 2.5mL of aqueous solution are dispersed into the above mixture and stirred until completely dissolved. Finally, the mixed solution is quickly poured into a rectangular silicone mold and heated at 60°C for 30 minutes to obtain a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel.

[0059] Embodiment 6:

[0060] First, add 1g of metal (gallium-indium alloy) to 5mL of deionized water, shake well, and use a cell disruptor to sonicate for 5min to obtain a uniformly dispersed liquid metal microsphere dispersion. Next, mix the above dispersion with 5mL of 4wt% sodium alginate solution, and then perform ultrasonic treatment for 5min to obtain an aqueous solution of sodium alginate encapsulated liquid metal. Subsequently, 2g of acrylamide monomer, 0.0065g of cross-linker N,N-methylenebisacrylamide, 0.015g of initiator ammonium persulfate, and 2.5mLMXene (2mg / mL) solution were dispersed into the above mixture and stirred until completely dissolved. Finally, the mixed solution was quickly poured into a rectangular silicone mold and heated at 60°C for 30 minutes to obtain a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel.

[0061] Embodiment 7:

[0062] First, add 1g of metal (gallium-indium alloy) to 5mL of deionized water, shake well, and use a cell disruptor to sonicate for 5min to obtain a uniformly dispersed liquid metal microsphere dispersion. Next, mix the above dispersion with 5mL of 4wt% sodium alginate solution, and then perform ultrasonic treatment for 5min to obtain an aqueous solution of sodium alginate encapsulated liquid metal. Subsequently, 2g of acrylamide monomer, 0.0065g of cross-linker N,N-methylenebisacrylamide, 0.015g of initiator ammonium persulfate, and 2.5mLMXene (7mg / mL) solution were dispersed into the above mixture and stirred until completely dissolved. Finally, the mixed solution was quickly poured into a rectangular silicone mold and heated at 60°C for 30 minutes to obtain a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel.

[0063] Embodiment 8:

[0064] First, add 1g of metal (gallium-indium alloy) to 5mL of deionized water, shake well, and use a cell disruptor to sonicate for 5min to obtain a uniformly dispersed liquid metal microsphere dispersion. Next, mix the above dispersion with 5mL of 4wt% sodium alginate solution, and then perform ultrasonic treatment for 5min to obtain an aqueous solution of sodium alginate-encapsulated liquid metal. Subsequently, 2g of acrylamide monomer, 0.0065g of cross-linker N,N-methylenebisacrylamide, 0.015g of initiator ammonium persulfate, and 2.5mLMXene (14mg / mL) solution are dispersed into the above mixture and stirred until completely dissolved. Finally, the mixed solution is quickly poured into a rectangular silicone mold and heated at 60°C for 30 minutes to obtain a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel.

[0065] Embodiment 9:

[0066] First, add 1.5g of metal (gallium-indium alloy) to 5mL of deionized water, shake well, and use a cell disruptor to sonicate for 5min to obtain a uniformly dispersed liquid metal microsphere dispersion. Next, mix the above dispersion with 5mL of 4wt% sodium alginate solution, and then perform ultrasonic treatment for 5min to obtain an aqueous solution of sodium alginate encapsulated liquid metal. Subsequently, 2g of acrylamide monomer, 0.0065g of cross-linker N,N-methylenebisacrylamide, 0.015g of initiator ammonium persulfate, and 2.5mL of aqueous solution are dispersed into the above mixture and stirred until completely dissolved. Finally, the mixed solution is quickly poured into a rectangular silicone mold and heated at 60°C for 30 minutes to obtain a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel.

[0067] Embodiment 10:

[0068] First, add 1.5g of metal (gallium-indium alloy) to 5mL of deionized water, shake well, and use a cell disruptor to sonicate for 5min to obtain a uniformly dispersed liquid metal microsphere dispersion. Next, mix the above dispersion with 5mL of 4wt% sodium alginate solution, and then perform ultrasonic treatment for 5min to obtain an aqueous solution of sodium alginate-encapsulated liquid metal. Subsequently, 2g of acrylamide monomer, 0.0065g of cross-linker N,N-methylenebisacrylamide, 0.015g of initiator ammonium persulfate, and 2.5mLMXene (2mg / mL) solution were dispersed into the above mixture and stirred until completely dissolved. Finally, the mixed solution was quickly poured into a rectangular silicone mold and heated at 60°C for 30 minutes to obtain a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel.

[0069] Embodiment 11:

[0070] First, add 1.5g of metal (gallium-indium alloy) to 5mL of deionized water, shake well, and use a cell disruptor to sonicate for 5min to obtain a uniformly dispersed liquid metal microsphere dispersion. Next, mix the above dispersion with 5mL of 4wt% sodium alginate solution, and then perform ultrasonic treatment for 5min to obtain an aqueous solution of sodium alginate-encapsulated liquid metal. Subsequently, 2g of acrylamide monomer, 0.0065g of cross-linker N,N-methylenebisacrylamide, 0.015g of initiator ammonium persulfate, and 2.5mLMXene (7mg / mL) solution were dispersed into the above mixture and stirred until completely dissolved. Finally, the mixed solution was quickly poured into a rectangular silicone mold and heated at 60°C for 30 minutes to obtain a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel.

[0071] Embodiment 12:

[0072] First, add 1.5g of metal (gallium-indium alloy) to 5mL of deionized water, shake well, and use a cell disruptor to sonicate for 5min to obtain a uniformly dispersed liquid metal microsphere dispersion. Next, mix the above dispersion with 5mL of 4wt% sodium alginate solution, and then perform ultrasonic treatment for 5min to obtain an aqueous solution of sodium alginate encapsulated liquid metal. Subsequently, 2g of acrylamide monomer, 0.0065g of cross-linker N,N-methylenebisacrylamide, 0.015g of initiator ammonium persulfate, and 2.5mLMXene (14mg / mL) solution were dispersed into the above mixture and stirred until completely dissolved. Finally, the mixed solution was quickly poured into a rectangular silicone mold and heated at 60°C for 30 minutes to obtain a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel.

[0073] Embodiment 13:

[0074] First, add 2g of metal (gallium-indium alloy) to 5mL of deionized water, shake well, and use a cell disruptor to sonicate for 5min to obtain a uniformly dispersed liquid metal microsphere dispersion. Next, mix the above dispersion with 5mL of 4wt% sodium alginate solution, and then perform ultrasonic treatment for 5min to obtain an aqueous solution of sodium alginate encapsulated liquid metal. Subsequently, 2g of acrylamide monomer, 0.0065g of cross-linker N,N-methylenebisacrylamide, 0.015g of initiator ammonium persulfate, and 2.5mL of aqueous solution are dispersed into the above mixture and stirred until completely dissolved. Finally, the mixed solution is quickly poured into a rectangular silicone mold and heated at 60°C for 30 minutes to obtain a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel.

[0075] Embodiment 14:

[0076] First, add 2g of metal (gallium-indium alloy) to 5mL of deionized water, shake well, and use a cell disruptor to sonicate for 5min to obtain a uniformly dispersed liquid metal microsphere dispersion. Next, mix the above dispersion with 5mL of 4wt% sodium alginate solution, and then perform ultrasonic treatment for 5min to obtain an aqueous solution of sodium alginate-encapsulated liquid metal. Subsequently, 2g of acrylamide monomer, 0.0065g of cross-linker N,N-methylenebisacrylamide, 0.015g of initiator ammonium persulfate, and 2.5mLMXene (2mg / mL) solution are dispersed into the above mixture and stirred until completely dissolved. Finally, the mixed solution is quickly poured into a rectangular silicone mold and heated at 60°C for 30 minutes to obtain a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel.

[0077] Embodiment 15:

[0078] First, add 2g of metal (gallium-indium alloy) to 5mL of deionized water, shake well, and use a cell disruptor to sonicate for 5min to obtain a uniformly dispersed liquid metal microsphere dispersion. Next, mix the above dispersion with 5mL of 4wt% sodium alginate solution, and then perform ultrasonic treatment for 5min to obtain an aqueous solution of sodium alginate encapsulated liquid metal. Subsequently, 2g of acrylamide monomer, 0.0065g of cross-linker N,N-methylenebisacrylamide, 0.015g of initiator ammonium persulfate, and 2.5mLMXene (7mg / mL) solution are dispersed into the above mixture and stirred until completely dissolved. Finally, the mixed solution is quickly poured into a rectangular silicone mold and heated at 60°C for 30 minutes to obtain a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel.

[0079] Embodiment 16:

[0080] First, add 2g of metal (gallium-indium alloy) to 5mL of deionized water, shake well, and use a cell disruptor to sonicate for 5min to obtain a uniformly dispersed liquid metal microsphere dispersion. Next, mix the above dispersion with 5mL of 4wt% sodium alginate solution, and then perform ultrasonic treatment for 5min to obtain an aqueous solution of sodium alginate encapsulated liquid metal. Subsequently, 2g of acrylamide monomer, 0.0065g of cross-linker N,N-methylenebisacrylamide, 0.015g of initiator ammonium persulfate, and 2.5mLMXene (14mg / mL) solution are dispersed into the above mixture and stirred until completely dissolved. Finally, the mixed solution is quickly poured into a rectangular silicone mold and heated at 60°C for 30 minutes to obtain a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel.

[0081] For ease of understanding, the raw material variables of the above examples are summarized in Table 1 as follows:

[0082] Table 1 Summary of raw material variables for Examples 1 to 16

[0083] variable Amount of gallium-indium alloy used (g) MXene solution concentration (mg / mL) Example 1 0.5 0 Example 2 0.5 2 Example 3 0.5 7 Example 4 0.5 14 Example 5 1.0 0 Example 6 1.0 2 Example 7 1.0 7 Example 8 1.0 14 Example 9 1.5 0 Example 10 1.5 2 Embodiment 11 1.5 7 Example 12 1.5 14 Embodiment 13 2.0 0 Embodiment 14 2.0 2 Embodiment 15 2.0 7 Example 16 2.0 14

[0084] Comparative Example 1:

[0085] The comparative example does not contain liquid metal and MXene, and the preparation steps are:

[0086] 5 mL of 4 wt% sodium alginate solution, 2 g of acrylamide monomer, 0.0065 g of cross-linking agent N,N-methylenebisacrylamide, 0.015 g of initiator ammonium persulfate, and 2.5 mL of aqueous solution were dispersed into the above mixture and stirred until completely dissolved. The mixed solution was then quickly poured into a rectangular silicone mold and heated at 60°C for 30 minutes to obtain a sodium alginate / polyacrylamide composite hydrogel.

[0087] The present invention performs the following tests on Examples 1-16 and Comparative Example 1:

[0088] (1) The sample morphology was observed using a scanning electron microscope (SEM).

[0089] Figure 1 These are SEM characterization images of the sodium alginate-encapsulated liquid metal dispersion and the liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel finally obtained in Example 16 of the present invention; (a) (b) are SEM characterization images of the sodium alginate-encapsulated liquid metal dispersion; (c) (d) are SEM characterization images of the liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel.

[0090] Figure 1(a)(b) show different magnifications, showing SA@LM particles (liquid metal particles encapsulated by sodium alginate) with spherical morphology and a diameter of less than 10 μm, as well as a hydrogel network with a hierarchical porous structure, with large pores of about 10-30 μm in diameter and small pores of about 1-10 μm in diameter.

[0091] (2) EMI SE values ​​and electromagnetic parameters in the frequency range of 8.2-12.4 GHz were measured using a rectangular waveguide (32117) and a two-port network analyzer (3672B-S, Ceyear, China). The size of the test hydrogel sample was cut into 22.86 mm × 10.16 mm (length × width) in the test frequency range of 8.2-12.4 GHz (Xband). The S parameters (S 11 and S 22 ), and calculate the reflection (R), transmission (T), and absorption (A) power coefficients according to the following formulas.

[0092] R=|S 11 | 2 =|S 22 | 2 (1)

[0093] Among them, S 11 is the input reflection parameter, that is, the input return loss; S 22 is the output reflection parameter, that is, the output return loss.

[0094] T=|S 11 | 2 =|S 22 | 2 (2)

[0095] Among them, S 11 is the input reflection parameter, that is, the input return loss; S 22 is the output reflection parameter, that is, the output return loss.

[0096] A=1-RT (3)

[0097] Figure 2 It shows that the stress and strain of the comparison ratio are around 60 kPa and 600%, which is difficult to meet the application in complex scenarios.

[0098] Figure 3 It shows that the embodiments of the present application can be adjusted within the strain range of 2000%-5000%, and the stress can be adjusted within the range of about 50-300 kPa, which can meet the application requirements in complex scenarios.

[0099] Figure 4It shows that the hydrogel reaches the highest EMI SE value of 86.6dB when the conductive filler is 2g liquid metal and 14mg / ml MXene. It can be found that the shielding performance of the hydrogel itself is significantly improved due to the improvement of the conductive network and the addition of MXene. Due to the introduction of more diverse interfaces, the appropriate increase in liquid metal can greatly improve the EMI shielding performance of the hydrogel. At the same time, the shielding mechanism is dominated by reflection, but as the liquid metal and MXene content increase, the absorption coefficient A value also increases, indicating that the absorption ratio increases, meeting the needs of the future development of electromagnetic shielding materials.

[0100] (3) The hydrogel was directly attached to the fingers, wrists, elbows, knees, and chests of volunteers as sensors, and the electrical signals generated by the sensors when each part moved were recorded using a multimeter.

[0101] Figure 5 The flexible strain sensor of liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel monitors signals of various parts of the human body. In the figure, (a) is a schematic diagram of the island bridge structure. (b) is a schematic diagram of sensing under different stretching rates. (c) is the GF factor of liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel. (d)(e)(f)(g)(h)(i) are the flexible strain sensors of liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel in Example 16 monitoring signals of various parts of the human body, including (d) finger bending at different angles, (e) knee joint movement, (f) knee joint squat movement, (g) elbow joint movement, (h) rapid finger bending, and (i) heartbeat detection.

[0102] The present application obtains the sensing performance of PSLM hydrogel by testing the resistance change rate of PSLM composite hydrogel under different strains (150%, 400%, 600%, 1000% and 1200%). Figure 5 b) Due to the ultra-stretchable and flexible properties of PSLM composite hydrogel, it exhibits excellent sensing performance from low to high tensile strain ranges. The R / R0 value increases significantly with the increase of strain, and quickly returns to the initial state after strain recovery, showing excellent stability and reversibility. Figure 5c The high sensitivity of the PSLM composite hydrogel sensor is revealed by the strain factor (GF). GF gradually increases with strain from 1.65 at low strain rates (0-150%). When the applied strain is 150-800%, the GF increases by 2.68. When the strain is 800-1000%, the GF is 4.42, showing an increasing trend with the increase of strain. The present application also uses PSLM hydrogel as the conductor of the LED lamp to achieve the effect of a breathing lamp. These phenomena can be attributed to the fact that the uniformly dispersed LM droplets change from spherical to needle-shaped after stretching, increasing the conductive sites of the connected MXene nanosheets and forming a longer conductive path, reflecting the high sensitivity of the PSLM composite hydrogel. The PSLM composite hydrogel is attached to a part of the human body to detect real-time human activities and health conditions. When the PSLM composite hydrogel sensor is attached to a finger, the signals generated by the finger joints when bent at 0°, 30°, 60° and 90° can be monitored immediately. The finger keeps the corresponding angle unchanged, and the hydrogel can maintain the current signal. The knuckles are then straightened from 90° in two steps, the first step is to restore to 45°, and the second step is to completely restore to 0° ( Figure 5 d). The signal response of PSLM composite hydrogel perfectly verifies the finger recovery process, reflecting the good reversibility and stability of the hydrogel. Figure 5 As shown in h, the fingers are rapidly bent at different angles, and the PSLM composite hydrogel can perform surprising signal detection. Figure 5 e shows the hydrogel detection of knee bending at 90°. Figure 5 f's squat showed a difference in signal strength, mainly because the squat angle was greater than 90°. The hydrogel was attached to the elbow to detect the arm flexion action signal ( Figure 5 g). Figure 5 i shows the heartbeat signal detected by the PSLM composite hydrogel attached to the left chest. It can be seen that the signal fluctuates around 0.6%, proving the hydrogel's ability to detect tiny strains and vibrations. The above results show that strain sensors based on PSLM composite hydrogels have great potential in the application of flexible wearable electronic products.

[0103] (4) Use the hydrogel as a temperature sensor to record the electrical signals generated by changes in ambient temperature and human body temperature.

[0104] Figure 6The temperature sensor of liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel monitors the ambient temperature and human body signals. In the figure, (a) is a schematic diagram of the temperature sensor of liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel, (b) is the resistance change of the temperature sensor of liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel at different temperatures, (c) is the resistance change of the temperature sensor of liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel under the cycle of 20 degrees-60 degrees, (d) is the resistance change when ice and hot water approach the temperature sensor of liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel, and (e) is the resistance change of ice at a distance from liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel. The resistance change of acrylamide composite hydrogel temperature sensor at different distances, (f) is the resistance change of hot water at different distances from the liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel temperature sensor, (g) is the resistance change of the liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel temperature sensor under a cycle of 0 degrees-20 degrees, (h) is the different temperature detection ranges of the liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel temperature sensor, and (i) is the liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel temperature sensor detecting different human body temperatures.

[0105] like Figure 6 As shown in b, the present application heats the PSLM composite hydrogel from 20°C to 60°C, and by measuring the change in the electrical conductivity of the hydrogel, it is calculated that the TCR value of the PSLM composite hydrogel is -1.1%°C-1 (R2=0.996), indicating that the hydrogel has a negative temperature coefficient of resistance and a highly linear thermal response. Figure 6 c shows that the hydrogel sensor maintains a repeatable resistance signal for 5 cycles within a large temperature sensing range (20℃-60℃) without obvious signal drift, which proves the stability, repeatability and practicality of the PSLM composite hydrogel temperature sensor. This application can use this characteristic of the PSLM composite hydrogel temperature sensor to detect ambient temperature and locate cold / heat sources. First, ice cubes and a beaker filled with 40℃ water are momentarily brought into contact with the PSLM composite hydrogel temperature sensor, and the sensor's resistance signal changes momentarily ( Figure 6 d). Keep the ice cube and the beaker in contact for about 22s and 26s respectively. Then remove the ice cube and the beaker. Due to the long contact time, the PSLM composite hydrogel temperature sensor recovers in about 1min. Figure 6As shown in Figure e, ice cubes are used alone to locate the cold source. When the ice cube gradually approaches the PSLM composite hydrogel temperature sensor, the resistance gradually increases with the distance, and different resistance signals are shown at different distances. This response occurs instantaneously and can accurately reflect the location of the cold source. A beaker filled with 40°C water is used alone to locate the cold source. When the beaker gradually approaches the PSLM composite hydrogel temperature sensor, the resistance gradually decreases with the distance, and different resistance signals are shown at different distances. This response occurs instantaneously and can accurately reflect the location of the heat source ( Figure 6 f).

[0106] The practical application of PSLM composite hydrogel temperature sensor also needs to meet the requirements of wide range of detection capability and repeatability. Specifically, the cyclic simulation was carried out for 3 experimental cycles between 0℃ and 40℃ ( Figure 6 g) An almost constant response was obtained in 3 cycles, indicating good durability. The PSLM composite hydrogel temperature sensor was heated to 100°C in an environment of 0°C and still showed a highly linear thermal response. In order to further explore the detection range of the hydrogel, this application found that the minimum detection could reach 0.1°C by controlling the heating temperature, which can meet the requirements of human body temperature monitoring ( Figure 6 h). Therefore, this application tests the response of the PSLM composite hydrogel temperature sensor within the human body temperature range (36.5℃-41℃). Due to its excellent thermal sensitivity, the signal changes can be observed within the narrow human body temperature range ( Figure 6 i).

[0107] The above experiments prove that the PSLM composite hydrogel temperature sensor is excellent in temperature detection range sensitivity, resolution, cold / heat source detection response speed and stability, reflecting its commendable application potential.

[0108] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel material, characterized in that: The composite hydrogel material includes a hierarchical porous structure and an "island bridge" structure; the hierarchical porous structure is composed of a network reinforced by liquid metal microspheres and a hydrogel double network, and the pores of the hierarchical porous structure are 5 to 20 μm; the "island bridge" structure is composed of liquid metal microspheres and MXene nanosheets, and the MXene nanosheets are uniformly distributed in the hydrogel network to form an "island bridge" structure with the liquid metal microspheres.

2. A method for preparing a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel material, characterized in that: The following steps are involved: S1. Add liquid metal to deionized water, shake well, and use a cell disruptor to sonicate to obtain a uniformly dispersed liquid metal microsphere dispersion; S2. The liquid metal microsphere dispersion is mixed with a sodium alginate solution, and then subjected to ultrasonic treatment to obtain an aqueous solution of sodium alginate encapsulated liquid metal; S3. Dispersing acrylamide monomer, crosslinking agent, initiator and MXene solution into the aqueous solution of sodium alginate-encapsulated liquid metal and stirring until completely dissolved to obtain a mixed solution; S4. The mixed solution is quickly poured into the mold, and the hydrogel obtained after heating is a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel material.

3. The method for preparing a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel material according to claim 2, characterized in that: In step S1, the liquid metal is a gallium-indium alloy; the dosage of the liquid metal and deionized water is in the ratio of (0.5-2) g:5 mL; and the ultrasonic time of the cell disruptor is 5-10 min.

4. The method for preparing a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel material according to claim 2, characterized in that: In step S2, the concentration of the sodium alginate solution is 3-5wt%; the volumes of the liquid metal microsphere dispersion and the sodium alginate solution are equal; and the ultrasonic treatment time is 5-10 minutes.

5. The method for preparing a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel material according to claim 2, characterized in that: In step S3, the cross-linking agent is either N,N-methylenebisacrylamide or dimethyl sulfoxide; the initiator is either ammonium persulfate or sodium perbromide.

6. The method for preparing a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel material according to claim 2, characterized in that: The concentration of the MXene solution in step S3 is 0 to 14 mg / mL, and can be 0, the solvent is deionized water, and the solute is MXene material.

7. The method for preparing a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel material according to claim 6, characterized in that: The MXene material is obtained by chemically etching a MAX phase material, wherein the MAX phase material is any one of titanium aluminum nitride, chromium carbonitride, titanium trialuminum dicarbide, titanium dialuminum nitride, vanadium dialuminum carbide, molybdenum diiron boride or niobium dialuminum carbide.

8. The method for preparing a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel material according to claim 2, characterized in that: The dosage of the acrylamide monomer, the cross-linking agent, the initiator, the MXene solution and the aqueous solution of the sodium alginate-encapsulated liquid metal in step S3 is in the following relationship: (0.5-3) g: (0.0055-0.0075) g: (0.010-0.0020) g: (2-3) mL: 10 mL.

9. The method for preparing a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel material according to claim 2, characterized in that: The heating temperature in step S4 is 60-80° C. and the heating time is 30-60 minutes.

10. An application of a liquid metal / MXene / sodium alginate / polyacrylamide composite hydrogel material, characterized in that: The composite hydrogel material is used as a multifunctional integrated flexible electronic device for strain sensing and / or temperature sensing.

Citation Information

Patent Citations

  • Hydrogel composite material as well as preparation method and application thereof

    CN115873367A

  • Liquid metal-coated MXene composite hydrogel photoresponse self-sensing driver and preparation method thereof

    CN117069965A

  • Functional filler / gallium-based liquid metal plasticine and preparation method thereof

    CN118854111A

  • Two-dimensional metal carbide, nitride, and carbonitride films and composites for EMI shielding

    US20190166733A1

Cited By

  • Electromagnetic shielding composite material and electromagnetic shielding sheet

    CN121335084A

  • Preparation method and application of MXene / liquid metal-based flexible composite film

    CN121687649A

  • Method for preparing mxene / liquid metal-based flexible composite film and application thereof

    CN121687649B

  • MXene and polyurethane synergistically modified micro-phase separation dual-network hydrogel as well as preparation method and application thereof

    CN121914500A